Stimulate The Growth of Rice Using Endophytic Bacteria from Lowland Rice Plant Tissue - Nuni Gofar; Hary Widjajanti; Neni Marlina (Faculty of Agriculture, Universitas Sebelas Maret, 2015)
Exploration and selection of endophytic bacteria from healthy food crops grown in lowland ecosystem is important to be conducted in order to get growth-stimulating endophytic bacteria at soil with low fertility level so that capable to optimize initial growth of food crops and subsequently can increase productivity level of lowland soil.The research objective was to isolate and to test the IAA-producing endophytic bacteria isolate in stimulating the rice crop growth at lowland area. Endophytic bacteria are isolated from tissues of rice, corn and peanut crops which grown at shallow swamp land in Ogan Ilir and Ogan Komering Ilir Districts, South Sumatra, Indonesia. There was nine isolates of nitrogen-fixer endophytic bacteria that capable to contribute IAA phytohormone into their growth media. The P31 isolate from rice crop tisssue of 2 months old produce the best rice sprouts than other isolates. This isolate can contribute of about 10 mg kg-1 IAA to its growth medium and increase the crowns dry weight and the roots dry weight respectively with magnitudes of 133% and 225% compared to control treatment. Concentration and absorbtion of N for rice crops innoculated with P31 isolates had increased by 169% and 400%, recpectively. The P31 isolates had been identified as Burkholderia pseudomallei (also known as Pseudomonas pseudomallei).